2018
DOI: 10.21037/jtd.2018.10.36
|View full text |Cite
|
Sign up to set email alerts
|

Patient and procedural features predicting early and mid-term outcome after radical surgery for non-small cell lung cancer

Abstract: Background: Postoperative cardiovascular and pulmonary complications (PCVCs and PPCs) are frequent and result in prolonged hospital stay. The aim of this study was to update the risk factors associated with major complications and survival after lung cancer surgery. Methods: This is a post-hoc analysis of a randomized controlled trial that was designed to assess the benefits of preoperative physical training. After enrollment, clinical, biological and functional data as well as intraoperative details were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…One explanation for the higher rate of complications in our study is that we included all types of complications. We report postoperative complications routinely and extensively, which could increase the number of complications [17, 18]. In addition, the higher rate of patient comorbidities in our study, as compared to some other studies, could increase the rate of complication, as established in the European risk models for morbidity (Eurolung1) score [19].…”
Section: Discussionmentioning
confidence: 96%
“…One explanation for the higher rate of complications in our study is that we included all types of complications. We report postoperative complications routinely and extensively, which could increase the number of complications [17, 18]. In addition, the higher rate of patient comorbidities in our study, as compared to some other studies, could increase the rate of complication, as established in the European risk models for morbidity (Eurolung1) score [19].…”
Section: Discussionmentioning
confidence: 96%
“…(McMillan 2014) Not only short-term but also long-term survival after lung resection surgery is significantly influenced by the occurrence of PPCs. 5 Several risk factors for PPCs after lung surgery have been identified. These are increased age, gender, pre-operative forced expiratory volume in 1 second (FEV 1 ) ≤ 60%, duration of surgery, body mass index (BMI) ≥ 30 kg/m 2 , smoking, ASA score ≥3, chronic obstructive lung disease (COPD) and increased intraoperative fluid administration.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with those found in this study. 2,3 Ellenberger et al 29 showed that a direct relationship between poor pre-operative physical performance and postoperative pulmonary complications. It has been shown that patients with lung cancer, who are at risk of poor physical function preoperatively may benefit from physiotherapy to improve physical function before surgery to prevent postoperative pulmonary complications, shorten hospital length of stay and lower in-hospital cost.…”
Section: Discussionmentioning
confidence: 99%